2009
DOI: 10.1007/s00423-009-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

CT-MIBI-SPECT image fusion predicts multiglandular disease in hyperparathyroidism

Abstract: Multiglandular disease in primary hyperparathyroidism can be suspected preoperatively in a high percentage of patients. Additionally, this study shows that CT-MIBI-SPECT image fusion is superior to CT or MIBI-SPECT alone in preoperative localization of all pathologic glands in patients suffering from multiglandular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 19 publications
(24 reference statements)
0
33
0
3
Order By: Relevance
“…The following year, SPECT/CT depicted ectopic parathyroid glands in 4 patients, aiding surgical planning (231). The utility of SPECT/CT for detection of cervical parathyroid adenomas has been confirmed in multiple subsequent SPECT/CT studies in primary, secondary and tertiary hyperparathyroidism, subgroups of patients with concurrent nodular thyroid disease, multigland disease, and in those with previously failed surgery (232)(233)(234)(235)(236)(237)(238)(239)(240)(241)(242)(243)(244)(245)(246)(247)(248)(249). Regardless of the protocols used, parathyroid scintigraphy SPECT/CT has been found to improve sensitivity and specificity for detection of single adenomas, providing key preoperative localization information.…”
Section: Parathyroid and Thyroid Scintigraphy With Spect/ctmentioning
confidence: 93%
See 1 more Smart Citation
“…The following year, SPECT/CT depicted ectopic parathyroid glands in 4 patients, aiding surgical planning (231). The utility of SPECT/CT for detection of cervical parathyroid adenomas has been confirmed in multiple subsequent SPECT/CT studies in primary, secondary and tertiary hyperparathyroidism, subgroups of patients with concurrent nodular thyroid disease, multigland disease, and in those with previously failed surgery (232)(233)(234)(235)(236)(237)(238)(239)(240)(241)(242)(243)(244)(245)(246)(247)(248)(249). Regardless of the protocols used, parathyroid scintigraphy SPECT/CT has been found to improve sensitivity and specificity for detection of single adenomas, providing key preoperative localization information.…”
Section: Parathyroid and Thyroid Scintigraphy With Spect/ctmentioning
confidence: 93%
“…SPECT/CT has sensitivities ranging from 70% to 100% and specificities from 83% to 100%; these vary depending on cohort studied, protocols used, surgical follow-up, study design and whether patient-or lesion-based analysis was used (232)(233)(234)(235)(236)(237)(238)(239)(240)(241)(242)(243)(244)(245)(246). SPECT/CT is clearly more sensitive than planar imaging.…”
Section: Image Interpretationmentioning
confidence: 99%
“…CT and SPECT datasets were acquired separately and then fused by means of special image fusion software allowing a ''virtual neck exploration'' by showing the suspected gland three-dimensionally in relationship to anatomical landmarks. The same authors also used this acquisition protocol in selected series of patients with single-gland disease or MGD at their first surgical exploration [51,52], comparing SPECT/CT image fusion with CT and SPECT alone. These studies provided evidence that SPECT/CT is superior to the other two diagnostic procedures for the preoperative localization of enlarged parathyroid glands.…”
Section: Spect/ct In Patients With Previous Neck Surgerymentioning
confidence: 99%
“…Pre-operative imaging did not locate any ectopic or supernumerary glands in any of the 30% of the patients who had one [65]. A recent study by Wimmer et al [66] found that computed tomography-(99m)Tc-sestamibi-single photon emission computed tomography (CT-MIBI-SPECT) image fusion identified abnormal glands in 46.7% (14/30) of the patients with multiglandular disease of any type. CT scan alone found all glands in 36.7% (11/30) and MIBI-SPECT alone in 13.3% (4/30) of patients.…”
Section: Pre-operative Imagingmentioning
confidence: 99%